Challenges of Modern Childhood: Key Outcomes of the National Strategy on Action for Children - Rubtsov V.V; Semya G.V; Shvedovskaya A.A (Moscow State University of Psychology and Education, 2018)
The article presents the results of the monitoring Key Outcomes of the National Strategy on Action for Children for 2012-2017, commissioned by the Ministry of Education and Science of the Russian Federation by the Moscow State Psychological University of Psychology and Education. The main results of the implementation of the six main directions of the implementation of the National Strategy are discussed: "Family Childhood Saving Policy", "Access to Quality Education and Upbringing, Cultural Development and Information Security for Children", "Healthcare Friendly to Children and Healthy Lifestyles", "Equal Opportunities for Children, who need special care of the state", "Creating a system of protection and ensuring the rights and interests of children and child-friendly justice"," Children - participants in the implementation of the National Strategy gii".The goals and tasks of the Decade of Childhood proclaimed by the President of the Russian Federation are considered.